Henry Cisneros being interviewed - Unknown:::Creator::::::::::::
Photograph shows a close up of Henry Cisneros, Secretary of Housing and Urban Development, being interviewed by reporters possibly at the Villa Nueva opening ceremony. There is a microphone with "14" on it and another microphone with "48 Telemundo" in the photograph. The back of a reporter's head is also visible.